2017
DOI: 10.1080/13803395.2017.1285869
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation improves working memory performance

Abstract: Vagus nerve stimulation (VNS) is used for treating refractory epilepsy and major depression. While the impact of this treatment on seizures has been established, its impact on human cognition remains equivocal. The goal of this study is to elucidate the immediate effects of vagus nerve stimulation on attention, cognition, and emotional reactivity in patients with epilepsy. Twenty patients (12 male and 8 female; 45 ± 13 years old) treated with VNS due to refractory epilepsy participated in the study. Subjects p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 49 publications
5
98
2
1
Order By: Relevance
“…Another study of 20 subjects investigating the effects of VNS on attention, cognition, and emotional reactivity found that subjects had improved working memory performance with VNS . More specifically, patients were presented with a triangle pointed upward or downward and had to recall its orientation when prompted by a visual cue.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 20 subjects investigating the effects of VNS on attention, cognition, and emotional reactivity found that subjects had improved working memory performance with VNS . More specifically, patients were presented with a triangle pointed upward or downward and had to recall its orientation when prompted by a visual cue.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the vagus nerve impair memory 12 , whereas pairing vagal nerve stimulation with auditory stimuli reorganizes neural circuits 43 , strengthens neural response to speech sounds in the auditory cortex 44 , and enhances extinction learning of fear memories in rodents 45 . In humans, vagal nerve stimulation enhances consolidation of verbal memory 13 and working memory 46 . Recently, Whitehurst and colleagues used traditional methods to detect total sympathetic and parasympathetic power of the HRV signal during sleep and showed a correlation between parasympathetic activity during REM sleep (but not SWS) and implicit learning 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall effect of VNS on cognition is unclear, and many studies focus on memory. There is an evidence that VNS treatment can acutely improve memory in a short time, but there seems to be no significant improvement within the long‐term treatment . Orosz et al surveyed the effects of VNS treatment on 347 pediatric patients, evaluating the different aspects of cognition such as memory, concentration, alertness, language communication, and academic progress at 12 and 24 months.…”
Section: Applicationmentioning
confidence: 99%
“…There is an evidence that VNS treatment can acutely improve memory in a short time, but there seems to be no significant improvement within the long-term treatment. [44][45][46] Orosz et al 31…”
Section: Appli C Ati Onmentioning
confidence: 99%